2019
DOI: 10.5812/hmj.86970
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Family Psychoeducation Intervention on Relapse Prevention in Hospitalized Psychiatric Patients

Abstract: Background: Family psychoeducation is considered as an intervention focused on individual rehabilitation of mental disorders through improving the caregiver's awareness about their family member's illness, risk factors, and treatment component and relapse prevention strategies. Objectives: The aim of this study was to determine the impact of family psychoeducation on patients' relapse and length of stay in hospital. Methods: In this retrospective study, registered data in the health information management unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…En cuanto a las actividades de prevención del reingreso, y asociado con esta revisión, se incluyen acciones con el paciente y la familia; sin embargo, un estudio de 2019 recomienda como acción adicional la estrategia de psicoeducación familiar que mejora la conciencia del trastorno y brinda herramientas de afrontamiento (46). Asimismo, un estudio exploratorio reportó baja adherencia terapéutica, por lo que los autores informan que abordar de manera humanizada la asistencia con apoyo de tecnología contribuye a mejorar la atención y la confianza entre profesionales, pacientes y familia (36).…”
Section: Discussionunclassified
“…En cuanto a las actividades de prevención del reingreso, y asociado con esta revisión, se incluyen acciones con el paciente y la familia; sin embargo, un estudio de 2019 recomienda como acción adicional la estrategia de psicoeducación familiar que mejora la conciencia del trastorno y brinda herramientas de afrontamiento (46). Asimismo, un estudio exploratorio reportó baja adherencia terapéutica, por lo que los autores informan que abordar de manera humanizada la asistencia con apoyo de tecnología contribuye a mejorar la atención y la confianza entre profesionales, pacientes y familia (36).…”
Section: Discussionunclassified
“…Similarly, the last study performed at a psychiatric hospital in Iran clarifies that family psycho-education is used as an intervention for patients with a mental illness by strengthening the awareness of the situation, risk factors, and recovery strategies for reducing relapse by the caregiver and families. 4049 participants were committed to a one-session individual family psychoeducational intervention directly after discharge 27 .. The seventh study was done in England at a mental health clinic.…”
Section: Cont Table 2: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…In addition, FFT-CHR provides a three-module module that focuses on the ability of patients and their families to cope with psychotic symptoms. The last study was carried out by Niksalehi et al 27 . The results showed that family psycho-education can have a major impact on the risk of readmission and the period of hospital stay.…”
Section: Evaluation Of the Effect Of Used Relapse Prevention Intervention On Ability Of Patients And Their Families To Prevent Psychotic mentioning
confidence: 99%
See 1 more Smart Citation